KARAKTER GURU DALAM IMPLEMENTASI MERDEKA BELAJAR DI MTS LABORATORIUM UIN SUMATERA UTARA - Sayyidah, Nayyara Parsa; Azkiyah, Nurul; Khairani, Elma; Siregar, Hestiyani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research investigates the implementation of teacher character within the Freedom to Learn (Independent Learning) concept, focusing on the perceptions of both teachers and students at MTs Laboratorium UIN Sumatera Utara. The teacher characteristics examined include responsibility, discipline, exemplary conduct, empathy, curriculum adaptability, and moral commitment, all deemed essential for successful teaching and learning processes. The Freedom to Learn concept aims to provide freedom in determining innovative and student-centered learning methods, yet its success fundamentally relies on the teacher's character and professionalism. This curriculum demands that teachers create a pleasant and participatory learning environment, with flexibility in assessment and the use of diverse learning resources. Challenges in implementing Freedom to Learn are identified, encompassing teacher human resource readiness, infrastructural limitations, and shifts in educational paradigms. Therefore, this study also identifies sustainable development strategies for teachers, with the aspiration that holistic teacher character development can optimize Freedom to Learn and foster students' full potential. ABSTRAKPenelitian ini mengkaji implementasi karakter guru dalam konsep Merdeka Belajar yang berfokus pada persepsi guru dan siswa di MTs Laboratorium UIN Sumatera Utara. Karakter guru yang diteliti meliputi tanggung jawab, kedisiplinan, keteladanan, empati, kemampuan adaptasi kurikulum dan komitmen moral yang esensial untuk keberhasilan proses belajar mengajar. Konsep Merdeka Belajar bertujuan memberikan kebebasan dalam menentukan metode pembelajaran yang inovatif dan berpusat pada peserta didik, namun keberhasilannya sangat bergantung pada karakter dan profesionalitas guru. Kurikulum ini menuntut guru menciptakan suasana belajar yang menyenangkan, partisipatif, serta fleksibilitas dalam penilaian dan penggunaan sumber belajar. Tantangan dalam implementasi Merdeka Belajar diidentifikasi mencakup kesiapan sumber daya manusia, guru, keterbatasan infrastruktur, dan perubahan paradigma. Oleh karena itu, penelitian ini juga mengidentifikasi strategi pengembangan berkelanjutan bagi guru, dengan harapan pengembangan karakter guru yang holistik dapat mendukung optimalisasi Merdeka Belajar dan pengembangan potensi peserta didik.